2014
DOI: 10.4236/ajps.2014.514230
|View full text |Cite
|
Sign up to set email alerts
|

Germination, Vigor of Seeds and Emergence of Fabaceae Seedling in Bovine Faeces

Abstract: This study was conducted to evaluate the physiological quality of forage seeds after passage through the gastrointestinal tract of cattle, as well as the emergence of seedlings derived from these seeds. Three Fabaceae species were used: tropical kudzu, leucaena and calopo. One hundred grams of seeds of each species were offered, separately, to five bovines. After the start of the dispersion, the faeces of the animals were collected every 6 hours, in a total of 72 hours, being taken to the greenhouse immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results of this study demonstrate that ruminants can neutralize the negative impact of grazing by the return of viable seeds in their droppings. Lima et al (2014) evaluated the physiological quality of forage seeds after passage through the gastrointestinal tract of cattle, as well as the emergence of seedlings derived from these seeds, the tropical kudzu, leucaena and calopo. The best performance for the total number of seedlings in the feces of cattle was observed in the kudzu species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study demonstrate that ruminants can neutralize the negative impact of grazing by the return of viable seeds in their droppings. Lima et al (2014) evaluated the physiological quality of forage seeds after passage through the gastrointestinal tract of cattle, as well as the emergence of seedlings derived from these seeds, the tropical kudzu, leucaena and calopo. The best performance for the total number of seedlings in the feces of cattle was observed in the kudzu species.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the classical view that the passage of seeds through the digestive tract of animals helps the germination process, some studies have pointed out that the effects of digestion on germination can vary considerably. The germination capacity may increase, decrease, or remain unchanged, compared with not-swallowed seeds (Figueroa and Castro, 2002;Lima et al, 2014). Seed properties such as the hardness of seed coat, seed size, shape and specific gravity are important to the survival of seeds passing through the digestive tract of livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [16] evaluating the germination and the vigor of Kudzu, Leucaena and Calopogônio seeds after the passage through the gastrointestinal tract (GIT) from bovines, observed that Kudzu seeds are less susceptible to the damages caused by the chewing and degradation in the GIT, once a higher emerged plant number in bovine feces was formed, as well as higher root lengths and aerial part and higher weight of natural and dry mass from the plants when compared to other species.…”
Section: Resultsmentioning
confidence: 99%